WELL-KNOWN POLISH PROVERBS IN INTERNET MEMES - Kozioł-Chrzanowska, Ewa (Proverbium - Yearbook, 2017)
The article analyzes the ways of using well-known Polish proverbs in the Internet memes. The research has been based on the lists of the Polish paremiological minima (gathered in 1998 and 2013). Proverbs taken from these lists were searched by the Google Images and, as a result, a corpus of 750 paremiological Internet memes was gathered. The paper takes into consideration quantitative as well as qualitative aspects of paremic memes. The former shows that there is no correlation between the big number of occurrences of the given proverbs on the paremiological minimum lists and their popularity among meme creators. The latter focuses on the relations between verbal (proverbs) and graphic (drawings, photos) units joined together in memes, e.g.: combinations of a proverb and a picture, which confirms the sense of the proverb, collations in which the picture is linked to one of the lexical ingredients of the proverb and graphic forms connected with particular kinds of transformations in proverbs (e.g. the image of master Yoda from “Star Wars” changing the word order). The results of the analysis indicate that meme creators know well the most popular of these units judging by the fact that the gathered corpus is quite big (750 examples) and covers most of the proverbs from the minimum list (62 out of 78). It can also be stated that proverbs have become a part of the new linguistic environment on the Internet, which is proved e.g. by the proverbs’ behavior according to the rules established by the Internet meme series). Some conclusions referring to the issue of the paremiological minimum have also been presented.